1988
DOI: 10.1177/104438948806900401
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Work with Suicidal Adolescents and Their Families

Abstract: The authors discuss psychosocial factors associated with three phases that lead to adolescent suicide attempts, assessment of risk, and treatment implications. Special focus is accorded to integrating individual treatment with family therapy or group therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Finally, higher levels of con ict and lower levels of warmth in the family were related to suicide ideation, consistent with previous ndings (e.g., Williams & Lyon, 1976;Hepworth, Farley, & Grif ths, 1988). In homes with high emotional instability, adolescents are unable to develop the coping skills to manage their dif cult environment and interpersonal skills in the development of successful friendships.…”
supporting
confidence: 88%
“…Finally, higher levels of con ict and lower levels of warmth in the family were related to suicide ideation, consistent with previous ndings (e.g., Williams & Lyon, 1976;Hepworth, Farley, & Grif ths, 1988). In homes with high emotional instability, adolescents are unable to develop the coping skills to manage their dif cult environment and interpersonal skills in the development of successful friendships.…”
supporting
confidence: 88%
“…On the other hand, drugs affect them directly or indirectly, regardless of age, gender, culture, ethnic background, education, race, or socioeconomic status (Flisher et al, 1993a;Williams, Ansell, & Milne, 1997). They create emotional highs and a counterfeit sense of well-being that temporarily supplant such pressures and feelings (Hepworth, Farley, & Griffiths, 1988). The use of drugs for personal gratification and temporary adaptation carries a very high price: drug dependence, personal and social disorganization, and a predisposition to serious and sometimes fatal diseases and accidents (Gullotta, Adams, & Montemayor, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…By the early 1990s, about one in nine deaths was shown to be tobacco related in South Africa (25,000 per year) (Yach, Mcintyre, & Saloojee, 1992). Lung cancer death rates increased by 100% among coloured men and 300% among coloured women over the period 1968-1988(Ehrlich & Bourne, 1994. Recent studies indicate that smoking prevalence exceeds 50% among African and coloured men and among coloured women; is less than 10% among African and Asian women; and, while high in the past, is decreasing among whites (Yach et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in youth suicide rates during the last few decades have been reported in many countries, including Australia [7]. Some authorities [8][9][10] have noted the parallel increases of psychoactive substance use and youth suicide and have suggested that the two are causally linked. Consistent with this suggestion, studies in different countries [11][12][13][14][15][16][17][18] have identified psychoactive substance abuse by adolescents as a high risk factor for suicidal behaviour.…”
Section: Introductionmentioning
confidence: 99%